Current view of vitamin D in pregnant women: a review - Chrisostomo,Kadija Rahal (2019)
Hypovitaminosis D is a global health problem that affects all age groups. Pregnant women are considered a high-risk group and the condition has potentially associated maternal and fetal complications. The goal of the present review is to analyze the magnitude and consequences of hypovitaminosis D in pregnant women and the safety of vitamin D supplementation. Prevalence of hypovitaminosis D during pregnancy is very high, even in sunny countries. Maternal vitamin D deficiency has been associated with increased risk of specific hypertensive disease of pregnancy, bacterial vaginosis, prematurity, gestational diabetes mellitus, osteomalacia, and muscle weakness. It has also been linked to prematurity, low birth weight, and fetal infectious complications. Due to potential maternal and fetal complications, it is extremely important to achieve adequate vitamin D levels prior to pregnancy. During pregnancy, it would be prudent to monitor serum vitamin D levels and implement preventive measures to reduce maternal and fetal morbidity. No consensus exists in the medical literature regarding vitamin D supplementation in pregnant women.